Implementation of Supreme Court Regulation Number 3 of 2022 concerning electronic mediation in the jurisdiction of The Denpasar District Court - Dewi, Ni Putu Laria; Sihotang, Erikson; Saputra, Komang Edy Dharma (Indonesian Journal of Multidisciplinary Science, 2024)
The integration of electronic systems into the judicial process represents a significant advancement in legal practice. The advent of e-Court and electronic mediation represent a broader trend towards integrating technology to improve the efficiency and reach of judicial processes. This study aims to find out the stages of implementation of Supreme Court Regulation Number 3 of 2022 concerning Electronic Mediation in the jurisdiction of the Denpasar District Court, and the inhibiting factors of the implementation of the regulation in this jurisdiction. The study provides valuable insights into the practical application of electronic mediation, highlights challenges faced in the field, and offers recommendations for improving the regulatory process and overcoming obstacles. This research could evaluate how legal representatives support parties in fulfilling their rights and obligations during electronic mediation. Additionally, investigating the specific obstacles related to software and human resources could provide insights into how these challenges impact the mediation process.